Electrical installation design for 13 storey apartment block / Mohamad Fadli Abdul Rahman - Abdul Rahman, Mohamad Fadli (2008)
This project is about design of electrical installation of 13 storey apartment block which has been prepared with reference to wiring regulations and there are interpretations of particular technicalities. The scopes of the design are calculation of power consumptions, estimate of range of power, lighting installation, MATV (master antenna TV) and telephone. As far as possible all information accords with the requirements of BS 7671: 2001 Requirements for Electrical Installation, the IEE Wiring Regulations. Issued jointly by British standards institution, the Electricity Regulation, Federations of Malaysia, and Tenaga Nasional Berhad (TNB). Besides that every item of equipment, which forms parts of an electrical installation, must be designed and manufactured so that it will be safe to use by consumer.